2015
DOI: 10.5380/dma.v33i0.37241
|View full text |Cite
|
Sign up to set email alerts
|

Farmacopeia natural de comunidades rurais no estado do Piauí, Nordeste do Brasil

Abstract: Artigo recebido em 26 de julho de 2014, versão final aceita em 6 de abril de 2015. RESUMO:Objetivou-se conhecer as plantas medicinais, as formas de usos e indicações terapêuticas atribuídas pelas comunidades Pau-Arrastado, Salinas e Resolvido. Utilizaram-se entrevista semiestruturada e turnês guiadas e seguiu-se metodologia botânica usual. Amostraram-se 93 pessoas (51,9% do total Palavras-chave: etnobotânica; Campo Maior; comunidades rurais. ABSTRACT:The purpose of this work is to know more about medicinal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
8
Order By: Relevance
“…The female respondents also reported using a greater amount of NUS for medicinal purposes, nine of the aforementioned species, while men reported using six of them. Silva et al [ 58 ] carried out a survey on plants used as medicines in rural communities in Piauí, Brazil, and found that women had a fundamental role in the cultivation and use of these vegetables, as well as in the maintenance of having a more specific knowledge of herbs and shrubs used in homemade therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The female respondents also reported using a greater amount of NUS for medicinal purposes, nine of the aforementioned species, while men reported using six of them. Silva et al [ 58 ] carried out a survey on plants used as medicines in rural communities in Piauí, Brazil, and found that women had a fundamental role in the cultivation and use of these vegetables, as well as in the maintenance of having a more specific knowledge of herbs and shrubs used in homemade therapy.…”
Section: Resultsmentioning
confidence: 99%
“…After the bark, the fruits are the most commonly used plant parts in the form of teas, bottled and macerated, for the treatment of diarrhea, liver, and kidney problems, pain (throat, legs, spine, and tooth), uterine inflammation, anemia, gastritis and urinary infection, as well as cicatrizing [ 29 , 35 , 41 , 43 , 44 , 47 ]. The seed tea is used to treat flus and coughs, and when immersed in water it is used as a cicatrizing agent [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diante disso, os estudos etnobotânicos são uma importante ferramenta de resgate e valorização desses conhecimentos. Adicionalmente, esses saberes representam a base para estudos descritivos das comunidades, ao indicar como seus integrantes utilizam as plantas na alimentação, construção, manufatura, rituais, medicina popular, entre outros fins (Fonseca & Sá 1997, Albuquerque 2005, Silva et al 2015a, Bastos et al 2018.…”
Section: Antecedentesunclassified